2020
DOI: 10.1126/sciadv.aaw8113
|View full text |Cite
|
Sign up to set email alerts
|

N-induced lattice contraction generally boosts the hydrogen evolution catalysis of P-rich metal phosphides

Abstract: The HER activities of P-rich transition metal phosphides can be substantially boosted by N-induced lattice contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(95 citation statements)
references
References 53 publications
(56 reference statements)
8
85
0
Order By: Relevance
“…In particular, the electrochemically active surface area of all the nanoparticles should be quantified by further investigation, in order to compare the catalysts based on a similar number of active sites. Besides, as suggested by a recent work on phosphorus-rich phosphides, [13] characterizing the adsorption strength of H species on the amorphous vs.…”
Section: Comparative Electrocatalytic Activity Of the Nanoscaled Ironmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, the electrochemically active surface area of all the nanoparticles should be quantified by further investigation, in order to compare the catalysts based on a similar number of active sites. Besides, as suggested by a recent work on phosphorus-rich phosphides, [13] characterizing the adsorption strength of H species on the amorphous vs.…”
Section: Comparative Electrocatalytic Activity Of the Nanoscaled Ironmentioning
confidence: 95%
“…In the past decades, transition metal phosphides have raised huge interest as promising nanomaterials. [1,2] They outperform their corresponding metal nanoparticles with respect to physical phenomena such as magnetism [3] or optics, [4] and show superior properties in applications relevant to energy storage, [5][6][7] and catalysis, [8][9][10][11][12][13][14][15] including water splitting. [16,17] In particular, Fe x P nanoparticles are among the most active catalysts containing an earthabundant metal to mediate the Hydrogen Evolution Reaction (HER) in acidic, [8,[18][19][20][21] neutral, [8] or basic media.…”
Section: Introductionmentioning
confidence: 99%
“…Ap lot of the electron density difference (Figure 5b) displays that the donation of electrons from the Ag 2 Se to nearby Co sites occurs at the interface,w hich permits e gorbital occupancyo fC oc loser to unity and thus enhanced OER activity, [31,36] matching well with our XANES measurements.M oreover,t he calculated projected density of states (PDOS;F igure 5c)shows that the d-band center of Co atom in Ag 2 Se-CoOOH deviates more from the Fermi level than that of single CoOOH (01-12), further evidencing the weak binding of *OH intermediate on the Ag 2 Se-CoOOH interfaces. [38] We also computed the OH binding energies of CoOOH and Ag 2 Se-CoOOH for comparison. Results in Figure 5d uncover ag reatly weakened OH adsorption on the interface sites.Moreover,our calculations further predict that the Co À Obond length increases from 1.763 to 1.882 on the Ag 2 Se-CoOOH interface (Insets in Figure 5d), again evidencing the weaker *OH adsorption on Ag 2 Se-CoOOH interface relative to CoOOH.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…High-resolution TEM (HRTEM) results showed that the inter-planar spacing of N-Cu is 2.166 Å, slightly larger than that (2.113 Å) of commercial Cu (Com-Cu). As the N anion possesses a larger ionic radius than Cu ion, the insertion of N may cause the lattice expansion [35]. These structural distortions were further validated by the powder Xray diffraction (XRD).…”
mentioning
confidence: 93%